2012
DOI: 10.3174/ajnr.a2921
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Cerebral Arteriovenous Malformations by 4D-MRA for Preoperative Planning and Postoperative Follow-Up in 56 Patients: Comparison with DSA and Intraoperative Findings

Abstract: BACKGROUND AND PURPOSE: 4D-MRA is a promising technique in the diagnosis and follow-up of cAVMs. The purpose of this study was to compare 4D-MRA in the pre-and postoperative evaluation of cAVMs with DSA or intraoperative findings as the standards of reference regarding qualitative and quantitative parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
(39 reference statements)
0
30
0
Order By: Relevance
“…In addition, temporal and spatial resolution can be further improved up to an acceleration factor of 60 by optimizing the use of intelligent k-space sampling techniques (ie, CENTRA, parallel imaging, and partial Fourier imaging), whereas our examinations had an acceleration factor of 40, equivalent to other recent publications. 17,[19][20][21]28,31 Second, the interobserver agreement for DSA was not as high as expected compared with 4D-MRA, though it was very good ( 0.84, 95% CI .69 -.98 and 0.82, 95% CI .67-.98, respectively) for the reasons explained above.…”
Section: Residual Nidusmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, temporal and spatial resolution can be further improved up to an acceleration factor of 60 by optimizing the use of intelligent k-space sampling techniques (ie, CENTRA, parallel imaging, and partial Fourier imaging), whereas our examinations had an acceleration factor of 40, equivalent to other recent publications. 17,[19][20][21]28,31 Second, the interobserver agreement for DSA was not as high as expected compared with 4D-MRA, though it was very good ( 0.84, 95% CI .69 -.98 and 0.82, 95% CI .67-.98, respectively) for the reasons explained above.…”
Section: Residual Nidusmentioning
confidence: 96%
“…Hadizadeh et al 21 recently concluded an excellent correlation between 4D-MRA and DSA regarding pre-and postoperative evaluation of bAVM, suggesting that 4D-MRA could be substituted for DSA in these 2 indications. However, in this series, of the 25 patients who had been followed-up after treatment, only 1 patient presented residual venous drainage.…”
Section: Residual Nidusmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low temporal resolution can also make delineation of small arterial feeders and venous drainage difficult with these techniques. 39 …”
mentioning
confidence: 99%
“…This results in deviations, albeit minor, in image contrast ("flickering"). Taking these limitations into account, a temporal resolution of 572 ms at a simultaneous spatial resolution of (1.1 × 1.1 × 1.1) mm³ was achieved when 4D-TRAK+ was used for examining cAVM, for example, while imaging all cranial blood vessels [41].…”
mentioning
confidence: 99%